Load testing for athletic training process control - Mekhdieva, K. R.; Zakharova, A. V.; Tarbeeva, V. M. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to substantiate the expediency of use of load testing toolkit with application of a gas analyzer for the management of the athletic training process.